Impact of an organic fertiliser on the yield of white cabbage (Brassica oleracea var. capitata) and the soil productivity - Danguolė Kavaliauskaitė; Rasa Karklelienė; Julė Jankauskienė (Horticultural Science, 2023)
The aim of this study was to determine the effect of a granular poultry manure fertiliser on the yield and the quality of white cabbage (Brassica oleracea var. capitata), and to determine the effect on the soil agrochemical properties. The effect of the granular poultry manure fertiliser and mineral fertiliser (applied separately and combined at different times - in early spring and in autumn) on the cabbage yields was determined. Investigations were carried out in the fields of the Institute of Horticulture, the Lithuanian Research Centre for Agriculture and Forestry. The object of the research - white cabbage 'Socrates' H. The highest white cabbage marketable yield (80.5 t/ha) and the highest amount of vitamin C (7.80 mg per 100 g of products) was obtained by applying the granular poultry manure fertiliser in the autumn and the mineral fertiliser in the spring, where the granular poultry manure fertiliser applied in the early spring and the granular poultry manure fertiliser applied in the autumn with the mineral fertiliser applied in spring retained a higher content of humus (1.82-1.94%), organic carbon (1.06-1.12%) and total nitrogen (0.099-0.147%). The mineral nitrogen residue in the soil decreased when the cabbage was fertilised in the spring with the mineral fertiliser and when fertilised in the spring with the mineral fertiliser in combination with the granular poultry manure fertiliser by 8.1-10.8 kg/ha. The minimum content of nitrates in the heads of the white cabbage was found after using the granular poultry manure fertiliser in the autumn.